A new method of preparation of 2-hydroxy-3,5-dinitrobenzonitrile - Pešková, Markéta; Jansa, Petr; Macháček, Vladimír (Univerzita Pardubice, 2005)
The vicarious nucleophilic substitution VSNArH has been uesd to prepare 2-hydroxy-3,5-dinitrobenzonitrile from 3,5-dinitrobenzonitrile in one step in a yield of 34%. It was found that the raw reaction mixture contains the isomers 2-hydroxy-3,5-dinitrobenzonitrile and 4-hydroxy-3,5-dinitrobenzonitrile (along with hydrolysis productsof this substance) in a ratio of ca 3:1.
Keywords: 2-hydroxy-3,5-dinitrobenzonitril; přípravy; metody